Theories of multiculturalism : an introduction - Crowder, George (Jaipur : Rawat Publications, 2013)
"Multiculturalism is one of the most controversial ideas in contemporary politics. In this new book George Crowder examines some of the leading responses to multiculturalism, both supportive and critical, found in the work of recent political theorists. The book provides a clear introduction to a diverse array of thinkers who have engaged with multiculturalism. These include Will Kymlicka, whose account of cultural rights is seminal, liberal critics of multiculturalism such as Brian Barry and Susan Okin, and multiculturalist critics of liberalism including Charles Taylor, Iris Marion Young, James Tully and Bhikhu Parekh."--Page 4 of cover.
Universalism, relativism and culture -- Liberal rights to culture : Kymlicka's theory -- Liberal critics of cultural rights -- Nationalists and cosmopolitans -- Beyond liberalism? -- Democrats -- Value pluralists -- Global cultures -- A liberal-pluralist approach.
Includes bibliographical references (pages 220-234) and index.
Keywords: Multiculturalism; Multiculturalism; Multiculturalism; Multikulturelle Gesellschaft; Politics and Government